National surveillance for influenza and influenza-like illness in Vietnam, 2006–2010 - Nguyen, Yen T. (Vaccine, 2013)
Influenza virus infections result in considerable morbidity and mortality both in the temperate and tropical world. Influenza surveillance over multiple years is important to determine the impact and epidemiology of influenza and to develop a national vaccine policy, especially in countries developing influenza vaccine manufacturing capacity, such as Vietnam. We conducted surveillance of influenza and influenza-like illness in Vietnam through the National Influenza Surveillance System during 2006–2010. At 15 sentinel sites, the first two patients presenting each weekday with influenza-like illness (ILI), defined as fever and cough and/or sore throat with illness onset within 3 days, were enrolled and throat specimens were collected and tested for influenza virus type and influenza A subtype by RT-PCR. De-identified demographic and provider reported subsequent hospitalization information was collected on each patient. Each site also collected information on the total number of patients with influenza-like illness evaluated per week. Of 29,804 enrolled patients presenting with influenza-like illness, 6516 (22%) were influenza positive. Of enrolled patients, 2737 (9.3%) were reported as subsequently hospitalized; of the 2737, 527 (19%) were influenza positive. Across all age groups with ILI, school-aged children had the highest percent of influenza infection (29%) and the highest percent of subsequent hospitalizations associated with influenza infection (28%). Influenza viruses co-circulated throughout most years in Vietnam during 2006–2010 and often reached peak levels multiple times during a year, when >20% of tests were influenza positive. Influenza is an important cause of all influenza-like illness and provider reported subsequent hospitalization among outpatients in Vietnam, especially among school-aged children. These findings may have important implications for influenza vaccine policy in Vietnam.